#TITLE_ALTERNATIVE# - SILVANUS (NIM : 12113012), KEVIN
According to the strategic plan of the Ministry of Transportation in 2015-2019, the construction of railways is a priority that will be done in the period 2015-2019. One segment of the railway line of concern is the southern part of the Java railway line, the Cirebon-Kroya line. To create the path, the Ministry of Transportation plans to build several tunnels. One of them is the Notog tunnel located in Desa Notog, Kecamatan Patikraja, Kabupaten Banyumas. This tunnel construction using NATM method (New Austrian Tunneling Method) and tunnel will penetrate soft rock, so with condition like that hence needed stability analysis of tunnel opening hole during construction process. Tunnel stability analysis will be on 5 research points, namely STA 359 + 420, 359 + 469, 359 + 527, 359 + 552 and 359 + 598 using finite element method. At each point an observation is made during the pre-supported phase and after supporting according to the support type used in each tunnel segment. From this model will get big deformation and strength factor as a reference of tunnel stability analysis. The result of the modeling shows that after supporting installation, the value of the tunnel safety factor at all research points is greater than one. The magnitude of the displacements occurring at all points of the study also shows that after supporting, the displacement is smaller than the critical displacement. Based on two references it can be said that the support type installed in each research point works well and the tunnel can be stable during the construction process.